2013
DOI: 10.1210/en.2012-2029
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet-Mediated Lipotoxicity and Insulin Resistance Is Related to Impaired Lipase Expression in Mouse Skeletal Muscle

Abstract: Elevated expression/activity of adipose triglyceride lipase (ATGL) and/or reduced activity of hormone-sensitive lipase (HSL) in skeletal muscle are causally linked to insulin resistance in vitro. We investigated here the effect of high-fat feeding on skeletal muscle lipolytic proteins, lipotoxicity, and insulin signaling in vivo. Five-week-old C3H mice were fed normal chow diet (NCD) or 45% kcal high-fat diet (HFD) for 4 weeks. Wild-type and HSL knockout mice fed NCD were also studied. Whole-body and muscle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 63 publications
(74 reference statements)
4
49
0
Order By: Relevance
“…Six hour-fasted mice were injected intraperitoneally with a bolus of D-glucose at 2 g/kg (Sigma-Aldrich, Saint-Quentin Fallavier, France) and insulin 0.5 units/kg (Insuman Rapid; Sanofi, Paris, France) for glucose and insulin tolerance tests (GTT and ITT), respectively (29). Blood glucose levels were monitored from the tip of the tail with a glucometer (Accucheck; Roche, Meylan, France) at 0, 15, 30, 45, 60, and 90 min after injection.…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six hour-fasted mice were injected intraperitoneally with a bolus of D-glucose at 2 g/kg (Sigma-Aldrich, Saint-Quentin Fallavier, France) and insulin 0.5 units/kg (Insuman Rapid; Sanofi, Paris, France) for glucose and insulin tolerance tests (GTT and ITT), respectively (29). Blood glucose levels were monitored from the tip of the tail with a glucometer (Accucheck; Roche, Meylan, France) at 0, 15, 30, 45, 60, and 90 min after injection.…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
“…Blood glucose levels were monitored from the tip of the tail with a glucometer (Accucheck; Roche, Meylan, France) at 0, 15, 30, 45, 60, and 90 min after injection. Radiolabeled GTTs were performed as previously described (29).…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
“…According to Badin et al ( 66 ), in skeletal muscle of HFD-fed mice, CGI58 is induced, while ATGL expression is repressed. These authors report signifi cant changes in skeletal muscle DAG and membrane translocation of protein kinase C subtypes (PKC-and PKC-).…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…In the present study, we did not find any increase in plasma FFA levels following 3 d of HFD intake either at rest or during the post-exercise recovery phase; however, it cannot be ruled out that the increased FFA levels were offset by enhanced utilization of FFAs as a fuel following adaptation to the HFD. Some previous studies reported that insulin resistance in skeletal muscle induced by an HFD is associated with lower phosphorylated levels of the insulin signaling cascade (19,32,33). However, others showed that the lower glucose uptake in post-exercise skeletal muscle after HFD consumption is not always accompanied by an impairment of the insulin signaling cascade (18,34).…”
Section: Discussionmentioning
confidence: 95%
“…Insulin resistance in skeletal muscle induced by an HFD is associated with lower phosphorylated levels of the insulin signaling cascade (19,32,33); conflicting results were observed in post-exercise skeletal muscle of mice which were provided HFD for 2 or 4 wk (18,34). We determined total amounts and phosphorylation states of proteins which were involved in glucose uptake and glycogen synthesis after post-exercise glucose administration.…”
Section: Levels and Phosphorylated States Of Proteins Involved In Insmentioning
confidence: 99%